2010
DOI: 10.2147/ndt.s10593
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal auditory forward masking pattern in the brainstem response of individuals with Asperger syndrome

Abstract: Abnormal auditory information processing has been reported in individuals with autism spectrum disorders (ASD). In the present study auditory processing was investigated by recording auditory brainstem responses (ABRs) elicited by forward masking in adults diagnosed with Asperger syndrome (AS). Sixteen AS subjects were included in the forward masking experiment and compared to three control groups consisting of healthy individuals (n = 16), schizophrenic patients (n = 16) and attention deficit hyperactivity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In fact, these changes in wave V have a positive predictive value of 78% and a negative predictive value of 73% for wave V. These differences in subjects with ASD can be further illustrated with masking experiments. Such paradigms revealed abnormal interpeak latencies between waves I-V and III-V (Thivierge et al, 1990 ), the reduced amplitude of wave III (Källstrand et al, 2010 ), and asymmetric masking by contralateral noise (Khalfa et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these changes in wave V have a positive predictive value of 78% and a negative predictive value of 73% for wave V. These differences in subjects with ASD can be further illustrated with masking experiments. Such paradigms revealed abnormal interpeak latencies between waves I-V and III-V (Thivierge et al, 1990 ), the reduced amplitude of wave III (Källstrand et al, 2010 ), and asymmetric masking by contralateral noise (Khalfa et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The differences of functional measures of the brainstem such as ABR indicate some form of abnormality. A common ABR abnormality is in the peak III amplitude and/or latency (Tanguay et al, 1982;Källstrand et al, 2010;Magliaro et al, 2010;Dabbous, 2012;Ververi et al, 2015;Claesdotter-Knutsson et al, 2019) which is suggested to be an indicator of SOC (Moller, 2006) activity. Additionally, ABR abnormalities are also seen in animal models such as Fmr1 KO mice (Rotschafer et al, 2015), α7-nAChR KO mice (Felix et al, 2019), Cntnap2 KO rats (Scott et al, 2018) and PA (Strata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Amplitudes are not commonly examined, and results are inconsistent. A group found peak III amplitude to be lower for ASD when a forward masking condition was applied (Figure 2B; Källstrand et al, 2010) while two others found it to be higher (Ververi et al, 2015;Claesdotter-Knutsson et al, 2019). Another study found that the ASD group had higher correlation between right and left ears compared to the typically developing participants (Claesdotter-Knutsson et al, 2019) which could be related to difficulties in the processing of everyday sounds.…”
Section: Functional Studiesmentioning
confidence: 91%
See 2 more Smart Citations